The Influence of Item Characteristics on Acquiescence among Latino Survey Respondents. Issue 1 (February 2020) - Davis, Rachel E.; Lee, Sunghee; Johnson, Timothy P.; Conrad, Frederick; Resnicow, Ken; Thrasher, James F.; Mesa, Anna; Peterson, Karen E.
Acquiescence is often defined as the systematic selection of agreeable ("strongly agree") or affirmative ("yes") responses to survey items, regardless of item content or directionality. This definition implies that acquiescence is immune to item characteristics; however, the influence of item characteristics on acquiescence remains largely unexplored. We examined the influence of eight item characteristics on acquiescence in a telephone survey of 400 Latinos and non-Latino Whites: qualified wording, mental comparisons, negated wording, unfamiliar terms, ambiguous wording, knowledge accessibility, item length, and polysyllabic wording. Negated and ambiguous wording was associated with reduced acquiescence for the full sample as well as subsamples stratified by ethnicity and sociodemographic characteristics. This effect was strongest among younger, more educated, and non-Latino white respondents. No other item characteristics had a significant influence on respondent acquiescence. Findings from this study suggest that acquiescence may be affected by interactions between respondent and item characteristics.